2019
DOI: 10.1016/j.jtho.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Airway Inflammation Induced by Pembrolizumab in a Patient With NSCLC

Abstract: 3. Wang R, Hu H, Pan Y, et al. RET fusions define a unique molecular and clinicopathologic subtype of non-small-cell lung cancer. J Clin Oncol. 2012;30: 4352-4359. 4. Gautschi O, Milia J, Filleron T, et al. Targeting RET in patients with RET-rearranged lung cancers: results from the global, multicenter RET registry. J Clin Oncol. 2017;35:1403-1410. 5. Drilon AE, Subbiah V, Oxnard GR, et al. A phase 1 study of LOXO-292, a potent and highly selective RET inhibitor, in patients with RET-altered cancers [abstract]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…[ 3 ] On the other hand, Ogawa et al reported pembrolizumab-induced fatal CD8 + infiltrated asthma-like bronchitis in a patient with NSCLC. [ 4 ] Mitropoulou et al reported 2 cases of severe bronchitis attributable to nivolumab with or without ipilimumab in patients with melanoma and NSCLC. [ 5 ] Airway diseases such as asthma and bronchitis have been recognized as a new pattern of irAE; hence, asthma-like symptoms should be monitored when an anti-PD-1 antibody is administered.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] On the other hand, Ogawa et al reported pembrolizumab-induced fatal CD8 + infiltrated asthma-like bronchitis in a patient with NSCLC. [ 4 ] Mitropoulou et al reported 2 cases of severe bronchitis attributable to nivolumab with or without ipilimumab in patients with melanoma and NSCLC. [ 5 ] Airway diseases such as asthma and bronchitis have been recognized as a new pattern of irAE; hence, asthma-like symptoms should be monitored when an anti-PD-1 antibody is administered.…”
Section: Discussionmentioning
confidence: 99%
“…Main pulmonary toxicities hitherto described are organizing pneumonia, ground‐glass opacities, interstitial lesions, hypersensitivity pneumonitis, or nonspecific interstitial pneumonitis 7 . Some studies have reported that pulmonary toxicities can be fatal, as in the case of acute respiratory distress syndrome (ARDS), 8 or severe acute asthma 5 . Recently, during durvalumab therapy, Yamakasi et al described the appearance of a diffuse micronodular pattern, with predominantly ground‐glass micronodules 9 …”
Section: Discussionmentioning
confidence: 99%
“…Bronchial toxicities induced by anti‐programmed cell death protein‐1 (PD‐1)/PD‐L1 immunotherapy have rarely been reported and rather as an exacerbation of chronic obstructive pulmonary disease (COPD) 5,6 . Here, we report a case of a patient who developed a pattern of bronchiectasis with bronchiolitis during anti‐PD‐L1 treatment with a favorable outcome after discontinuation of immune checkpoint inhibitors (ICIs).…”
Section: Introductionmentioning
confidence: 99%
“…There are also case reports of Pembrolizumab-Related Pulmonary Infection Reactivation (TB), Fatal Steroid-Resistant Airway Inflammation (Severe Fatal Asthma Exacerbation), Alveolar Hemorrhage Related to Pembrolizumab, etc [22][23][24].…”
Section: Pulmonary Toxicitymentioning
confidence: 99%